THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. RODALINK INDO TAMA - Gunawan, Yanthi Meitry; Purwaningsih, Nining; Wahyudi, Dicky (Universitas Muhammadiyah Tangerang, 2025)
This study aims to determine the influence of Organizational Culture and Work Motivation on Employee Performance at PT. Rodalink Indo Tama (in the South Tangerang area). This study uses a quantitative approach. The population in this study is employees of PT. Rodalink Indo Tama (in the South Tangerang area) has a total of 60 employees, and samples were taken from the entire population. The sampling technique in this study uses non-probability (saturated sampling). The data source in this study uses primary data with observation, interview and questionnaire dissemination techniques measured by the Likert Scale, then processed using SPSS version 26. The results of this study show that partially, the variable of Organizational Culture has a positive and significant effect on employee performance, which is shown with a tcal value of 7.854>ttable 2.001 with a significant value of 0.000 (sig 0.000< α 0.05). For the variable of Work Motivation partially has a positive and significant effect which is shown by a tcal value of 10.554>ttable 2.001 with a significant value of 0.000 (sig 0.000< α 0.05). Simultaneously, Organizational Culture and Work Motivation have a positive and significant effect on Employee Performance shown by a value of Fcal 70.077 > Ftable 3.16 with a sig of 0.000 (sig 0.000 < 0.05).